2022
DOI: 10.3390/ijerph192214802
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Attention to Body Shape, Social Physique Anxiety, and Personal Characteristics of Brazilians: A Structural Equation Model

Abstract: People can develop eating disorders due to excessive body image concerns. The primary objective of this study was to examine the relationship between attention to body shape, social physique anxiety, and personal characteristics in a sample of Brazilians. The secondary objective was to evaluate the correlation of the constructs with the participants’ body composition. First, 1795 individuals (70% female; Mage = 25.5 ± 6.6 years) completed the Attention to Body Shape Scale, the Social Physique Anxiety Scale, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 44 publications
0
1
0
10
Order By: Relevance
“…Los estudios fueron realizados entre el año 2014 y 2023. De los cuales, cinco estudios se efectuaron en Noruega (Havnes et al, 2019;Havnes et al, 2020;Havnes et al, 2021;Scarth et al, 2020;Vaskinn et al, 2020), uno en Islandia (Gestdóttir et al, 2020), uno en Australia (Piatkowski et al, 2023), un estudio en España (Marti et al, 2017), uno en Finlandia (Vauhkonen et al, 2023) y uno en Brasil (Da Silva et al, 2022).…”
Section: Resultados Y Discusión Resultadosunclassified
See 3 more Smart Citations
“…Los estudios fueron realizados entre el año 2014 y 2023. De los cuales, cinco estudios se efectuaron en Noruega (Havnes et al, 2019;Havnes et al, 2020;Havnes et al, 2021;Scarth et al, 2020;Vaskinn et al, 2020), uno en Islandia (Gestdóttir et al, 2020), uno en Australia (Piatkowski et al, 2023), un estudio en España (Marti et al, 2017), uno en Finlandia (Vauhkonen et al, 2023) y uno en Brasil (Da Silva et al, 2022).…”
Section: Resultados Y Discusión Resultadosunclassified
“…La mayoría de los estudios incluyeron tanto a hombres como mujeres (Da Silva et al, 2022;Gestsdóttir et al, 2020;Havnes et al, 2020;Havnes et al, 2019;Martí et al, 2017;Piatkowski et al, 2023;Vaskinn et al, 2020) y solo tres estudios incluyeron exclusivamente a mujeres (Havnes et al, 2021;Scarth et al, 2022;Vauhkonen et al, 2023). Respecto a las edades de los participantes en cada una de los estudios, las muestras incluyen mayores de edad.…”
Section: Resultados Y Discusión Resultadosunclassified
See 2 more Smart Citations
“…Echoing Guo and colleagues' (2022) finding, this study observed that the pandemic-induced mask mandate accidentally functioned as a protection and security mechanism for participants who were anxious about their appearance. Moreover, as indicated in some recent studies, citizens' reduced frequency of daily outdoor activities during the epidemic prevented them from maintaining or achieving their ideal weight; these failed attempts at remaining fit in turn aggravated their negative feelings about themselves [59,60]. With their faces covered by the mask, individuals with a higher degree of appearance anxiety are likely to switch their attention to their body as suggested by main theme 4 ("Wearing masks shifts my attention from appearance to figure ").…”
Section: Discussionmentioning
confidence: 99%